Cassia grandis, Pink Shower - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS, 2012)
The name “pink shower” comes from the bright pink blossoms that this tree produces. It is sometimes called “stinking tree” because the pulp in its pods has a very strong smell. This 2-page fact sheet was written by Michael G. Andreu, Melissa H. Friedman, and Robert J. Northrop, and published by the UF Department of School of Forest Resources and Conservation, July 2012.